Chris Argyris: theories of action, double-loop learning and organizati onal learning - Smith, Mark K. (The encyclopedia of pedagogy, 2013)
Chris Argyris: theories of action, double-loop learning and organizati onal learning. The work of Chris Argyris (1923-2013) has influenced th inking about the relationship of people and organizations…